Designing a conceptual model to explain the job success of school counselors - sara Haghshenas; Khadijeh Abolmaali Alhoseini (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2022)
The purpose of this study was to develop a conceptual model for explaining the job success of school counselors. In this study, a mixed-method with a sequentially guided exploratory approach was used. In the qualitative part, the descriptive phenomenological method was used. In the qualitative part, the descriptive survey method was applied. the statistical population of the study consisted of school successful consultants in Tehran province in 1397-98, Which were about 1300 people. In the qualitative part, the sample was selected by‌ snowball purposeful method, and 10 people were examined until saturation. In a quantitative part, 300 people were selected conveniently and voluntarily. For Data collection was used semi-structural interview, in the qualitative part, and a researcher-made questionnaire on the job success of school counselors, in the qualitative part. Cronbach's alpha coefficient of this questionnaire was 0.81 and its face and content validity were confirmed using the opinion of experts. In the qualitative part, data analysis was performed, using the Colaizzi method, and in the quantitative part using confirmatory factor analysis with AMOS software. The results of the qualitative part, for the job success of consultants, were identified 5 categories, including that professional knowledge, application of knowledge, ability development, job / social interaction, and office activities. Also, the results of the quantitative part indicated the fit of the research measurement model with the collected data. I